A game-theoretic analysis of the government's role on the biomass supply chain construction. Issue 5 (4th July 2017) - Zhai, Mingling; Zhang, Xu; Cheng, Fei; Zhou, Xiang; Su, Xing
ABSTRACT: This research utilises a game-theoretic approach to model and analyse the biomass power supply chain. The problem of the government's policy-choosing is discussed based on the vertical interactions between the three players: the farmer, the biomass power plant, and the government. A sequential game with asymmetric information is established considering the core issues: whether the farmer supplies the biomass to the power plant, what the power plant's optimal purchasing price of the biomass is, and which policy the government chooses. The Nash equilibriums are obtained, and the factors affecting the Nash equilibriums are summarised. Based on the discussion of these factors, the model can be modified to mimic reality by some modifications. An extension will be to include more kinds of asymmetric information. Another extension will be to change the policy objective of the government. Special attention is devoted to the impact of the change of the policy objective, which is caused by the reality of the government's structure, on the Nash equilibrium results.